AN INSTRUMENT FOR MEASURING THE SOCIAL WILLINGNESS TO PAY FOR HEALTH STATE IMPROVEMENT. (4th July 2013) - Richardson, Jeff; Iezzi, Angelo; Sinha, Kompal; Khan, Munir A.; Mckie, John
ABSTRACT This paper describes an instrument for measuring the social value of changes in health status, the Relative Social Willingness to Pay. It is a unique combination of measurement attributes designed to minimise cognitive complexity and provide an additional option for measuring 'social value'. Similar to the person trade‐off (PTO), it adopts a social perspective and asks respondents to evaluate programmes on behalf of society. Unlike the PTO, trade‐offs between the options use dollars, not numbers of patients. Respondents are not, however, asked for their personal willingness to pay. Rather, the opportunity cost of funds spent on one service is as an offsetting reduction in funds for a second service. The amount spent on each service therefore indicates relative, not absolute, value. However, the two services combine to produce one Quality adjusted life year which allows the calculation of a Quality adjusted life year‐like unit of social value on a 0–1 scale. A three‐stage survey was used to test the instrument's reliability, validity and sensitivity to the framing of the main question. Results indicate that the Relative Social Willingness to Pay produces values similar to but less than the PTO and time trade‐off techniques. Copyright © 2013 John Wiley & Sons, Ltd.